Transient Neonatal Zinc Deficiency Caused by a Heterozygous G87R Mutation in the Zinc Transporter ZnT-2 (SLC30A2) Gene in the Mother Highlighting the Importance of Zn2+ for Normal Growth and Development. (29th September 2013) - Miletta, Maria Consolata; Bieri, Andreas; Kernland, Kristin; Schöni, Martin H.; Petkovic, Vibor; Flück, Christa E.; Eblé, Andrée; Mullis, Primus E.
Abstract : Suboptimal dietary zinc (Zn 2+ ) intake is increasingly appreciated as an important public health issue. Zn 2+ is an essential mineral, and infants are particularly vulnerable to Zn 2+ deficiency, as they require large amounts of Zn 2+ for their normal growth and development. Although term infants are born with an important hepatic Zn 2+ storage, adequate Zn 2+ nutrition of infants mostly depends on breast milk or formula feeding, which contains an adequate amount of Zn 2+ to meet the infants' requirements. An exclusively breast-fed 6 months old infant suffering from Zn 2+ deficiency caused by an autosomal dominant negative G87R mutation in the Slc30a2 gene (encoding for the zinc transporter 2 (ZnT-2)) in the mother is reported. More than 20 zinc transporters characterized up to date, classified into two families (Slc30a/ZnT and Slc39a/Zip), reflect the complexity and importance of maintaining cellular Zn 2+ homeostasis and dynamics. The role of ZnTs is to reduce intracellular Zn 2+ by transporting it from the cytoplasm into various intracellular organelles and by moving Zn 2+ into extracellular space. Zips increase intracellular Zn 2+ by transporting it in the opposite direction. Thus the coordinated action of both is essential for the maintenance of Zn 2+ homeostasis in the cytoplasm, and accumulating evidence suggests that this is also true for the secretory pathway of growth hormone.